Quantum Hall drag of exciton condensate in graphene - Liu, Xiaomeng; Watanabe, Kenji; Taniguchi, Takashi; Halperin, Bertrand I.; Kim, Philip (Nature physics, 2017)
An electronic double layer, subjected to a high magnetic field, can form an exciton condensate: a Bose–Einstein condensate of Coulomb-bound electron–hole pairs. Now, exciton condensation is reported for a graphene/boron-nitride/graphene structure. An exciton condensate is a Bose–Einstein condensate of electron and hole pairs bound by the Coulomb interaction 1 , 2 . In an electronic double layer (EDL) subject to strong magnetic fields, filled Landau states in one layer bind with empty states of the other layer to form an exciton condensate 3 , 4 , 5 , 6 , 7 , 8 , 9 . Here we report exciton condensation in a bilayer graphene EDL separated by hexagonal boron nitride. Driving current in one graphene layer generates a near-quantized Hall voltage in the other layer, resulting in coherent exciton transport 4 , 6 . Owing to the strong Coulomb coupling across the atomically thin dielectric, quantum Hall drag in graphene appears at a temperature ten times higher than previously observed in a GaAs EDL. The wide-range tunability of densities and displacement fields enables exploration of a rich phase diagram of Bose–Einstein condensates across Landau levels with different filling factors and internal quantum degrees of freedom. The observed robust exciton condensation opens up opportunities to investigate various many-body exciton phases.